Tyrannosaur Canyon - Preston, Douglas J.; Sowers, Scott (New York : Audio Renaissance, 2005)
Tom Broadbent is riding his horse through a New Mexico canyon when he comes upon a dying prospector who gives Tom a notebook filled with mysterious numbers, asking him to pass it on to his daughter. As Tom and his wife try to deliver the notebook, they soon find themselves involved in a race to find the intact skeleton of a Tyrannosaurus Rex.
Unabridged.
"Includes a bonus interview with the author"--Container.
Read by Scott Sowers.
Compact discs.
Keywords: New Mexico -- Fiction; Audiobooks; Science fiction